The Relationship between Leukocyte Count and Left Ventricular Ejection Fraction in Patients with ST-Elevation Myocardial Infarction - Muhammad Atha Muafa; Evi Supriadi; Fairuz; David Ramli; Hasna Dewi (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
ABSTRACT Background: ST-Elevation Myocardial Infarction (STEMI) causes significant myocardial damage and increases heart failure risk. Inflammation, reflected by leukocyte count, is considered to play a crucial role in STEMI's pathophysiology, potentially affecting cardiac function. This study aimed to evaluate the relationship between leukocyte count and left ventricular ejection fraction (LVEF) in STEMI patients. Methods: A cross-sectional study was conducted from August to September 2024 at RSUD Raden Mattaher Jambi. Data from 80 patient medical records, including leukocyte count at admission and LVEF measured via echocardiography, were analyzed using Fisher's Exact and Spearman's correlation tests. Results: Most patients were male (82.5%), with high leukocyte counts (67.5%) and low LVEF (82.5%). The mean age was 57.8 years. Prevalences of hypertension, diabetes, and dyslipidemia were 38.8%, 33.8%, and 47.5%, respectively. Statistical analysis revealed no significant relationship between leukocyte count and LVEF (Fisher's p=0.497; Spearman's p=0.078; r=0.16). Conclusion: This study found no significant association between leukocyte count and LVEF in STEMI patients. Keywords: STEMI; Leukocyte; Ejection fraction